DIAGENETIC STUDY BASED ON PETROGRAPHY: IMPLICATIONS FOR SANDSTONE POROSITY OF THE PEUNASU FORMATION, PULAU NASI, ACEH - Gunarsih, Dina; Sary, Cut Afriyana; Muhni, Akmal; Rahmatillah, Lia Fitria; Sartika, Dewi (Indonesian Physical Review, 2025)
Diagenetic studies observe the process of changing sedimentary deposits into sedimentary rocks. This study is critical because it relates to the quality of rock porosity, which can be filled by fluid. Â The analysis of the Peunasu Formation is interesting because previous researchers considered that the Tertiary sedimentary rocks in the Northwest Aceh Basin are equivalent to rock units in the petroleum system in the North Sumatra Basin and Mergui Basin. Meanwhile, studies on the Peunasu Formation, a tertiary sedimentary rock, still need to be completed. Therefore, this study was carried out to determine the characteristics and diagenetic processes in the sandstone of the Peunasu Formation. The method used is petrographic observation, which identifies the composition of rocks along with textures such as grain size, roundness, sorting, grain contact, and porosity. The results are that the Peunasu Formation sandstone is classified as sublitharenite, lithic greywacke, and litharenite. The diagenetic regime is mesogenesis. In the mesogenesis stage, the sandstone of the Peunasu Formation experiences compaction, cementation, and dissolution. The porosity of the Peunasu Formation sandstone, as determined by the percentage of pores, exhibits a range of 0.5% to 16.8%, categorizing it as ranging from negligible to moderate. Compaction reduces the intergranular porosity, while the dissolution of grains contributes to the formation of secondary porosity.